Rational design of a eutectic Ni-Al-Ti alloy composited with B2 and L12 intermetallics for elevated-temperature application - Mengqi Gao; Donghui Wen; Zhaowen Huang; Fengyu Kong; Junhu Liu; Qiang Li; Cong Zhang; Chain-Tsuan Liu; Anding Wang (Materials & Design)
Intermetallic alloys with ordered superlattice phases, e.g., B2-NiAl and L12-Ni3Al phases, possess unparalleled strength and structural stability at elevated temperatures, therefore are widely applied in aerospace and energy fields. Improving their castability and room-temperature brittleness is therefore of great significance. In this proof-of-concept study, Ni-Al-Ti alloys with B2 and L12 intermetallic phases were designed with the help of phase diagram calculation assists composition adjustment. The representative Ni-22Al-7Ti eutectic alloy with a dual-phase lamellar microstructure possesses an ultra-high fracture strength of 3500 MPa and an admirable fracture strain of 30 % under compression at room-temperature. It also possesses a super-high strength of 1180 MPa at 700 °C, overperforming their single-phase counterparts. The superior mechanical property can be attributed to the synergetic deformation of the eutectic structure, R characterization (abnormal yield effect) and the Ti alloying enhanced phase stability at elevated temperatures. The non-equilibrium solidification induced super-saturation also results in the super-high strength at room-to-medium temperature and a unique softening mechanism via the formation of the two-fold composite structure. These results provide a promising candidate alloy for elevated-temperature applications, and a new paradigm for dual-intermetallic eutectic alloy design.